Influence of Uveitis in developing Posterior Capsule Opacification in Patients with Phacoemulsification with Hydrophobic Intraocular Lens - Mozid, Abeed; Sultana, Zakia; Alam, Md Mahfuzul; Sarker, Sanjay Kumar; Roy, Subarna; Rashid, Md Abdur (Journal of National Institute of Ophthalmology, 2026)
Objective: To access the influence of uveitis in developing posterior capsule opacification (PCO) in patients who underwent phacoemulsification cataract surgery with hydrophobic intraocular lens. Methodology: This prospective observational study was conducted in cataract department of National Institute of Ophthalmology and Hospital, Dhaka from 1st January, 2022 to 31st December, 2022. After getting informed consent 53 eyes of 45 patients affected by uveitis who underwent phacoemulsification cataract surgery with hydrophobic intraocular lens aged 25-75 years were selected according to the selection criteria and underwent detailed history taking and ocular examination. Follow-up was given at 1, 3 and 6 months interval. PCO formation was assessed by slit lamp examination and data were recorded and analyzed by SPSS Statistics version 26 software. Results: Out of 53 eyes of 45 patients posterior capsule opacification (PCO) occurred in 21 eyes (39.62%). The occurrence more commonly seen in young (25-45 years) to middle aged (45-55years) adults than older (55-75years) adults and among them 30 (66.67%) patients were female and 15 (33.33%) patients were male. Conclusion: The study shows significant influence of uveitis in developing posterior capsule opacification (PCO) more commonly in young adult female patients who underwent phacoemulsification cataract surgery with hydrophobic intraocular lens which can help to guide prevention, awareness development and targeted intervention for the patients. J.Natl.Inst.Ophthalmol.2024;7(1): 24-28